When do wrestlers peak? - Curby, D. (2007)
When sports scientists look at a sport, they often develop a profile of the characteristics of the champions. It is interesting to note the age of wrestlers at the peak of their success. The ages of all Olympic wrestling champions were examined for this article. Birth dates were obtained for most champions on the FILA Database. The average age of all Olympic wrestling champions is 26.79 years. The freestyle average age is 26.42 and for Greco-Roman is 27.15. There are no dramatic trends apparent. The champions in Athens were a bit younger than the style average: Greco-Roman-24.38, Freestyle-25.21 and Women-20.88.